An Efficacious Endometrial Sampler for Screening Endometrial Cancer - Han, Lu; Du, Jiang; Zhao, Lanbo; Sun, Chao; Wang, Qi; Tuo, Xiaoqian; Hou, Huilian; Liu, Yu; Wang, Qing; Ulain, Qurat; Lv, Shulan; Zhang, Guanjun; et al. (Frontiers in Oncology, 2019)
Recently, the research on early detection of precancerous change and endometrial carcinoma has been focusing on minimally invasive procedures for screening. On this basis, we aim to verify the feasibility of endometrial samplers for screening endometrial cancer using Li Brush. We recruited patients undergoing hysterectomy for different diseases from the Inpatient Department of the Department of Obstetrics and Gynecology. Before surgery, endometrial cells were collected by Li Brush. The cytopathologic diagnosis from Li Brush and the histopathologic diagnosis from hysterectomy in the same patient were compared to calculate sensitivity (Se), specificity (Sp), false-negative rate (FNR), false-positive rate (FPR), positive predictive value (PV+) %, and negative predictive value (PV-). The research enrolled 293 women into this self-controlled trial. According to the hypothesis test of paired four lattices, we obtained the following indicators: Se 92.73%, Sp 98.15%, FNR 7.27%, FPR 1.85%, PV+ 92.73%, and PV- 98.15%. The endometrial sampler Li Brush is an efficacious instrument for screening endometrial cancer.